The role of gender in providing expert advice on cyber conflict and artificial intelligence for military personnel - Fisher, Kelly (Frontiers in Big Data, 2022)
This article draws upon original qualitative interview data with Norwegian male and female cyberengineer cadets at the Norwegian Cyber Defense Academy, who could in the future be working with AI-enabled systems in a variety of positions throughout the Norwegian military. The interviews explored how these cadets feel they as cyberengineers will be perceived in their future positions in the military, what challenges they feel they may face, and how gender may play a role in this. Different cyberengineers expressed concern about being able to communicate the cyber domain to their non-technology specialist colleagues due to the increasing complexity of new technologies. Gender appeared to be playing a role in this concern as the women interviewed expressed specific concerns that they feel as women, that they do not fit the stereotype of who is a cyberengineer, while some of the men felt that as cyberengineers they were seen as embodying a nerd masculinity, and that these gendered perceptions has implications for how they feel others perceive their competence levels. The findings from this article highlights gendered hierarchies in the military and the need for military institutions to focus on developing communication skills among those working with cyber operations. As the role of cyber is expected to grow in military operations, cyberengineers will need to find ways of communicating effectively with non-specialists—especially as complex AI-enabled systems are introduced. Finally, this paper argues the need for military institutions to take gender into account for this training and need for gender-sensitive policies.